The Effect Of Purple Sweet Potato Starch Variation On Marshmallow Characteristics - Ningsih, Ayu Puspita; Marlina, Lusi (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2024)
Purple sweet potato contains antioxidants such as beta-carotene and anthocyanins that have health benefits. This study utilizes purple sweet potato that has been processed into starch as a raw material for making marshmallows. This study aims to determine the best variation of purple sweet potato starch on marshmallow characteristics and its effect by referring to standards on soft confectionery. The research conducted was experimental with a Completely Randomized Design (CRD). The tests carried out include water content test, organoleptic test, acidity (pH) test and antioxidant activity. In the organoleptic test, there were significant differences in taste and texture, while in color and aroma, there were no significant differences. Hedonic test showed that panelists preferred the taste of marshmallows with 10 grams of purple sweet potato starch in sample a1. The best moisture content was found to be 17.74% in sample a1 dp and 17.81% in sample a2. The acidity (pH) value was found to be 6.88 in samples a1 and a1 dp and 6.5 in sample a3. Antioxidant activity in sample a1 was 50.11% and sample a3 was 38.73%. Based on the results of all tests, the results are in accordance with SNI 3547.2: 2008 Keywords: Marshmallow, Purple Sweet Potato Starch, Purple Sweet Potato, Kruskall Wallis Test, Variation of Purple Sweet Potato Starch